Dexmedetomidine Improves Non-rapid Eye Movement Stage 2 Sleep in Children in the Intensive Care Unit on the First Night After Laparoscopic Surgery - Zhang, Xian; Chang, Li; Pan, Shou-Dong; Yan, Fu-Xia (Frontiers in Pediatrics, 2022)
Background: Previous studies have reported that children who were admitted to the ICU experienced a significant decrease in sleep quality compared to home. We investigated the effects of dexmedetomidine as an adjunct to sufentanil on the sleep quality in children admitted to the ICU on the first night after major surgery. Methods: This is a prospective study From January to February 2022. Clinical trial number: ChiCTR2200055768, http://www.chictr.org.cn. Fifty-four children aged 1-10 years old children undergoing major laparoscopic surgery were recruited and randomly assigned to either the DEX group, in which intravenous dexmedetomi-dine (0.3 ug/kg/h) and sufentanil (0.04 ug/kg/h) were continuously infused intra-venously for postoperative analgesia; or the SUF group, in which only sufentanil (0.04 ug/kg/h) was continuously infused. Patients were monitored with poly-somnography (PSG) on the first night after surgery for twelve hours. PSG, sleep architecture, physiologic variables and any types of side effects related to anes-thesia and analgesia were recorded. The differences between the two groups were assessed using the chi-square and Wilcoxon rank-sum tests. Results: Fifty-four children completed data collection, of which thirty-four were 1-6 years old and twenty were aged > 6 years. Compared to the SUF group, subjects in the DEX group aged 1-6 years displayed increased stage 2 sleep duration (P = 0.02) and light sleep duration (P=0.02). Subjects aged >6 years in the DEX group also displayed increased stage 2 sleep duration (P = 0.035) and light sleep duration (P=0.018), but decreased REM sleep percentage (P = 0.). Additionally, the heart rate and blood pressure results differed between age groups, with the heart rates of subjects aged >6 years in DEX group decreasing at most time points compared to SUF group (P < 0.05). Conclusion: Dexmedetomidine prolonged N2 sleep and light sleep duration in the pediatric ICU after surgery but had different effects on the heart rate and blood pressure of subjects in different age groups.